Marketing : concepts and strategies - Pride, William M.; Ferrell, O. C. (Boston, Massachusetts : Houghton Mifflin Company, 1989)
A marketing textbook must change often to keep pace with new developments in the teaching and practice of marketing. In this edition, we focus on the concepts most relevant to the development and implementation of marketing strategies. To make the sixth edition as informative, accessible, complete, and interesting as possible.
Part I. An Analysis of Marketing Opportunities -- Part II. Product Decisions -- Part III. Distribution Decisions -- Part IV. Promotion Decisions -- Part V. pricing Decisions -- Part VI. Marketing Management -- Part VII. Selected Applications.
Includes index.
Keywords: MARKETING